Comparative Study of Human and Murine Aortic Biomechanics and Hemodynamics in Vascular Aging - Hopper, Sara E.; Cuomo, Federica; Ferruzzi, Jacopo; Burris, Nicholas S.; Roccabianca, Sara; Humphrey, Jay D.; Figueroa, C. Alberto (Frontiers in Physiology, 2021)
Aging has many known effects on the cardiovascular system, including changes in structure (aortic stiffening) and function (increased blood pressure). Mouse models are often used to gain insight into vascular aging and mechanisms of disease as they allow invasive assessments that are not practical in humans. However, translation of results obtained from murine models to humans can be limited due to species-specific anatomical, biomechanical, and hemodynamic differences that can lead to different patterns of vascular aging. In this study, we created fluid-structure interaction (FSI) models of the aorta, informed by biomechanical and imaging data, to compare biomechanics and hemodynamics in humans and mice at two equivalent ages in their lifespans: young and old adults. For the humans, patient-specific computational models were created using magnetic resonance imaging (MRI) and non-invasive hemodynamic data; for the mice, models were created using population-specific biomechanics, hemodynamics, and structural stiffness data. Global aortic hemodynamics, anatomy, and stiffness were compared between humans and mice across age. For the young adult subjects, we found differences between species in pulse pressure amplification, compliance and resistance distribution, and aortic stiffness gradient. We also found differences in the response to aging between species. Generally, the human spatial gradients of stiffness and pulse pressure across the aorta diminished with age, while they increased for the mice. These results highlight key differences in vascular aging between human and mice, and it is important to acknowledge these when using mouse models for cardiovascular research.